Pengaruh Faktor Komunikasi, SDM, Disposisi Dan Struktur Birokrasi Dalam CDAKB Serta Dampaknya Terhadap Kinerja Usaha PAK - Astuti, Dewi; Aritonang, MGS; Fuad Afdhal, Ahmad (State University of Gorontalo, 2024)
Medical devices are instruments, apparatus, machines and implants that do not contain drugs that are used to prevent, diagnose, cure and relieve disease, treat sick people, restore human health and form the structure and improve body function. In the Minister of Health Regulation Number 4 of 2014 article 2 paragraph (1) it is stated that